The food and environment we love; Examining the 'on-the-ground' application of the 4R Nutrient Stewardship in Ghana. Issue 1 (2023) - Boateng, Dickson; Atkinson, Christopher; Arthur-Holmes, Francis; Amoah, Evans Amoako
Abstract: The past few years have witnessed emphasis on food security and sustainable farming— Sustainable Development Goal 2, zero hunger. Discourse on food production highlight knowledge and sources of advice on fertilisers use appears to influence farmers' efficient application of fertilisers. Yet, the research literature is silent on farmers' knowledge of fertilisers, its use and impacts on the environment in sub-Saharan Africa. This paper sets out to investigate the knowledge farmers have on the environment and analyse if they apply fertilisers in an environmentally efficient manner. Data was pulled from face-to-face administered questionnaires with 635 farmers in the Offinso Municipality, Ghana. Results showed that 94.0% of the farmers did apply fertilisers. Further, 47.8% of the 594 farmers who applied fertilisers relied on their accumulated knowledge with none applying fertilisers in accordance with the 4R Nutrient Stewardship — right type, right place, right time, and right rate. However, 60.6% of those who applied fertilisers were not aware that the inefficient application of fertilisers could harm the environment. Although the key role of extension officers in sustainable farming was acknowledged by farmers, access to extension services remained a problem. This paper suggests that extension officers should be supported by the agricultural institutions and the government to implement the 4R Nutrient Stewardship guidelines at the ground level to promote sustainable farming. Also, extension officers seeking to promote sustainable farming must intensify efforts in disseminating information on the 4Rs to farmers to secure the food and protect the environment we love. Highlights: The cost of fertilisers is the most important criterion farmers consider in choosing the type of fertiliser to apply. Some farmers are unable to take advantage of storage and application guidelines due to low levels of literacy. Some farmers are unable to access extension officers and thus, apply fertilisers based on their accumulated knowledge. Not every farmer knows that the inefficient application of fertilisers causes harm to the environment. There is a policy gap in the implementation of the 4R Nutrient Stewardship since no farmer applies fertilisers in accordance with the guidelines.